ACTUAL ASPECTS OF TEACHING OF POLITOLOGY AT AGRARIAN HIGHER SCHOOL - Бабічєв, Є.Р. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 1970)
The paper concerns on role analysis of Politology in general outlook of modern specialist of agrarian sector of national economy. The problems arising in connection with Bologna system application at our higher school are in the focus of our attention. It is emphasized that the deepening the role of students' self-study work needs increasing the number of academic hours for the given subject for both seminars and practicals. The author elucidates this problem from the point of view of his own experience and the Politology Department experience.